Memórias da violência: uma análise comparativa de Duas vezes junho e K. relato de uma busca - Suttili, Diogo (2024)
This paper aims to analyze the novels Duas vezes junho (2005), by the Argentine author Martín Kohan, and K. Relato de uma busca (2022), by the Brazilian author Bernardo Kucinski, exploring the themes of memory and violence. Considering the memory of the dictatorship in both countries as a disputed space, it can be seen that in both works memory emerges from two perspectives: that of the groups that collaborated with the regime and that of those silenced by the repression. For this analysis, authors such as Maurice Halbwachs (2004), Paul Ricoeur (2008) and Pierre Nora (2012) were used. Dictatorial violence was observed both during authoritarian regimes and in the novels, encompassing not only torture and murder, but also power relations, bureaucracies and false information. Michel Foucault (1997, 1999), Pierre Bourdieu (1998, 1999) and Hannah Arendt (1999) were used as theoretical frameworks. With their fragmented narratives, the novels do not just follow one voice, but reveal the remains of a past that still reverberates. These works have become fundamental to Argentine and Brazilian literature, as they function as instruments that communicate the experiences lived during the dictatorship, keeping the memory of this trauma alive for all generations.